Any help is welcome :) only right answers get brainilest

Answer:
[tex]a_{n} =\frac{2}{3}*9^{n-1}[/tex]
Step-by-step explanation:
a1 = 2/3
an = 9*a(n-1)
a2 = 9 *a1 = 9* 2/3
a3 =9*a2 = 9 *(9*2/3) = 9²*2/3
a4 = 9*a3 = 9* (9²*2/3) = 9³*2/3
Explicit rule formula: a(n) = a · rⁿ⁻¹
a(n) = ⁿth term
a = first term
r = common ratio
ⁿ⁻¹ = the previous term
In the recursive rule a₁ = 2/3; aₙ = 9 · aₙ₋₁ the first term is 2/3 and the common ration is 9. We can fill in the explicit formula with what we know.
Thus, the correct answer is [ aₙ = 2/3 · 9ⁿ⁻¹ ]
Best of Luck!